An Elevated Mutation Frequency Favors Development of Vancomycin Resistance in Staphylococcus aureus - Schaaff, Franziska (American Society for Microbiology, 2002)
The emergence of intermediate vancomycin resistance, mainly in methicillin-resistant Staphylococcus aureus strains, has become a great concern. Thorough characterization of clinical and laboratory vancomycin-intermediately resistant S. aureus (VISA) strains identified multiple, resistance-associated changes most probably due to stepwise mutations. We hypothesized that an elevated mutation frequency as found, e.g., in mutator strains defective in DNA mismatch repair could allow rapid acquisition of adaptive mutations in the presence of vancomycin. We therefore subjected S. aureus RN4220 and its isogenic mutator strain, the mutS-knockout mutant RN4220ΔmutS, to a stepwise vancomycin selection procedure. Vancomycin resistance evolved much more quickly in the mutator background than in the wild type (5 versus 19 passages, respectively). In addition, a higher resistance level could be reached (MIC, 32 versus 4 μg/ml, respectively). The susceptibility to other antibiotics with the exception of teicoplanin remained unchanged. Concomitantly with increasing vancomycin resistance, a loss of phage typeability and differences in growth behavior as well as an improved ability to regrow at high vancomycin concentrations were observed. In conclusion, an elevated mutation rate in S. aureus led to the rapid development of vancomycin resistance, indicating that a high mutation frequency could be one of the factors that favor the emergence of vancomycin resistance in S. aureus.